KAJIAN TEKNIS LAMPU LED TYPE TABUNG DIBANDINGKAN DENGAN LAMPU TL - Slamet, Puji; Budiono, Gatut (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2016)
Judging from the development, the lights have undergone significantchanges. LED lamp is a very good product in overcoming the problems ofenergy saving electricity. How much savings compared to the use of LEDfluorescent lamp seems still makes a question that needs to be a research studyto find out. Located at the Faculty of Engineering, University of SurabayaAugust 17, 1945 we conducted research on how much the savings generated bythe use of multiple LED lamps compared to the use of multiple fluorescent lampin a room. The method used in the process of this study is to compare lampuTLand LED lights related to the intensity of the lighting, large power absorbed byeach lamp and how much difference the energy used existing fluorescent lampand LED lights that each sampled two types of lamps , Namely Tl lamps withpower 18 W and 36 W and LED lamp with a power of 10 W and 20 W. Theresults obtained in this study is that the intensity of lighting some LED lights1x20 Watt higher than with some fluorescent lamp 1x36 Watt, some lightingintensity LED lights 2x10 Watt higher than with some fluorescent lamp 2x18Watt. Meanwhile, when viewed from the use of electrical power, the electricalpower several LED lights 1x20 Watt is lower than the electric power severalfluorescent lamp 1x36 Watt and some electric power 2x10 Watt LED light islower than the electric power several fluorescent lamp 2x18 Watt. To review theuse of Energy showed that electrical energy consumption (KWH) a few LEDlamps (1x20 Watt) is lower than KWH a few fluorescent lamp (1x136 Watt) andelectrical energy consumption (KWH) a few LED lamps (2x10 Watt) lower thanKWH some TL lamps (2x18 Watt). The use of LED lamps in terms of someaspects of it can be instrumental in saving power consumption and electricalenergy.Keywords: LED lights, lamps TL, savings